Combined bimolecular fluorescence complementation and Förster resonance energy transfer reveals ternary SNARE complex formation in living plant cells - Kwaaitaal, Mark; Keinath, Nana; Pajonk, Simone (Plant physiology, 2010)
Various fluorophore-based microscopic methods, comprising Förster resonance energy transfer (FRET) and bimolecular fluorescence complementation (BiFC), are suitable to study pairwise interactions of proteins in living cells. The analysis of interactions between more than two protein partners using these methods, however, remains difficult. In this study, we report the successful application of combined BiFC-FRET-fluorescence lifetime imaging microscopy and BiFC-FRET-acceptor photobleaching measurements to visualize the formation of ternary soluble N-ethylmaleimide-sensitive factor attachment receptor complexes in leaf epidermal cells. This method expands the repertoire of techniques to study protein-protein interactions in living plant cells by a procedure capable of visualizing simultaneously interactions between three fluorophore-tagged polypeptide partners.
Gesehen am 29.06.2017